2005
DOI: 10.1172/jci22079
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gas6 receptors in platelet signaling during thrombus stabilization and implications for antithrombotic therapy

Abstract: Mechanisms regulating thrombus stabilization remain largely unknown. Here, we report that loss of any 1 of the Gas6 receptors (Gas6-Rs), i.e., Tyro3, Axl, or Mer, or delivery of a soluble extracellular domain of Axl that traps Gas6 protects mice against life-threatening thrombosis. Loss of a Gas6-R does not prevent initial platelet aggregation but impairs subsequent stabilization of platelet aggregates, at least in part by reducing "outsidein" signaling and platelet granule secretion. Gas6, through its recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(245 citation statements)
references
References 45 publications
12
230
2
1
Order By: Relevance
“…Gas6 -/-mice are found to be resistant to both arterial and venous thrombosis models 29,30 . Similar results were obtained with Axl/Tyro3/Mer -/-mice 31 . Additional studies in mice have suggested that Gas6 is important for endothelial activation, as Gas6 -/-animals showed impaired ICAM upregulation, as well as decreased adhesion by immune cells and platelets after exposure to tumor necrosis factor alpha 32 .…”
Section: Introductionsupporting
confidence: 87%
“…Gas6 -/-mice are found to be resistant to both arterial and venous thrombosis models 29,30 . Similar results were obtained with Axl/Tyro3/Mer -/-mice 31 . Additional studies in mice have suggested that Gas6 is important for endothelial activation, as Gas6 -/-animals showed impaired ICAM upregulation, as well as decreased adhesion by immune cells and platelets after exposure to tumor necrosis factor alpha 32 .…”
Section: Introductionsupporting
confidence: 87%
“…In addition to the roles discussed in this Review, TAM receptor signalling has been shown have important regulatory roles in vascular smooth-muscle homeostasis [92][93][94] , in platelet function and thrombus stabilization 23,95,96 , in erythropoiesis 97 and in cancer development and progression 19,98,99 . TAM receptors are also implicated in the regulation of osteoclast function 100,101 , in the control of oligodendrocyte cell survival 102,103 , and in the infection of dendritic cells and other cells by Ebola and Marburg viruses 104,105 .…”
Section: Box 1 | Tam Receptor Signalling In Other Tissues and Organsmentioning
confidence: 99%
“…TAM receptors are also implicated in the regulation of osteoclast function 100,101 , in the control of oligodendrocyte cell survival 102,103 , and in the infection of dendritic cells and other cells by Ebola and Marburg viruses 104,105 . In many of these instances, the primary downstream TAM signalling pathway appears to be the phosphoinositide 3-kinase-AKT pathway 95,97,99,102,103 , rather than the Janus kinase-STAT (signal transducer and activator of transcription) pathway that is highlighted in this Review.Because knockout of each of the TAM genes still produced viable and fertile mice, and because the Tyro3 and Mer genes are linked in the mouse genome, it was possible to generate knockout mice that were deficient for all three TAM receptors 20 . Remarkably, even these triple knockout mice were found to be viable at birth, and to be superficially normal for the first several weeks thereafter.…”
mentioning
confidence: 99%
“…Gas6 binds to three receptors on platelets, Tyro3, Axl and Mer, but genetic targeting of any one unexpectedly inhibits Gas6-induced platelet stimulation. However, as Gas6 also induces tyrosine phosphorylation of GP IIIa, apparently by a mechanism independent of binding to the integrin, it has been proposed that Gas-6 signaling could be therapeutically regulated through inhibition of Gas6-GP IIb-IIIa cross-talk [65].…”
Section: Secondary Aggregation Receptorsmentioning
confidence: 99%